Actually, when you know 2 sides and an included angle, you use the Law of Cosines. (and we don't know if theta is an included angle).
Solving for side c
c^2 = a^2 + b^2 -2ab * cos(C)
c^2 = 36 + 16 - 2*6*4 * cos(60)
c^2 = 52 -48*.5
c^2 = 28
c = 5.2915
Using the Law of Sines
side c / sin(C) = side b / sin (B)
5.2915 / sin(60) = 4 / sin (B)
sin(B) = sin(60) * 4 / 5.2915
sin(B) = 0.86603 * 4 / 5.2915
<span><span>sin(B) = 3.46412
</span>
/ 5.2915
</span>
<span><span><span>sin(B) = 0.6546571451
</span>
</span>
</span>
Angle B = 40.894 Degrees
sin (A) / side a = sin (B) / side b
sin (A) = 6 * sin (40.894) / 4
sin (A) = 6 * 0.65466 / 4
sin (A) = .98199
angle A = 79.109 Degrees
angle C = 60 Degrees
5 least common multiple is 5 nines is 3 and thirty's is 3
Answer: 684
Step-by-step explanation:
95% of 720
Move decimal point two places to the right.
0.95 * 720 = 684
Answer:
<em>The measure of angle J is 44°</em>
Step-by-step explanation:
<u>Isosceles Trapezoid</u>
The isosceles trapezoid has its non-parallel sides of the same length, thus the angles they form with their respective parallel sides are congruent.
It means: Angle J is congruent with angle K and angle M is congruent with angle L
The sum of angles in a trapezoid is 180*(4-2)=360°
Thus:
![m\angle J+m\angle K+m \angle M+m\angle L = 360^\circ](https://tex.z-dn.net/?f=m%5Cangle%20J%2Bm%5Cangle%20K%2Bm%20%5Cangle%20M%2Bm%5Cangle%20L%20%3D%20360%5E%5Ccirc)
![7x+2+7x+2+25x-14+25x-14=360](https://tex.z-dn.net/?f=7x%2B2%2B7x%2B2%2B25x-14%2B25x-14%3D360)
Joining like terms:
![64x-24=360](https://tex.z-dn.net/?f=64x-24%3D360)
Adding 24:
![64x=384](https://tex.z-dn.net/?f=64x%3D384)
Dividing by 64:
x=6°
Thus:
![m\angle J = 7*6+2=44^\circ](https://tex.z-dn.net/?f=m%5Cangle%20J%20%3D%207%2A6%2B2%3D44%5E%5Ccirc)
![m\angle M = 25*6-14=136^\circ](https://tex.z-dn.net/?f=m%5Cangle%20M%20%3D%2025%2A6-14%3D136%5E%5Ccirc)
The measure of angle J is 44°
Solution:
The difference of cubes identity is
if a and b are any two real numbers, then difference of their cubes , when taken individually:
→a³ - b³= (a-b)(a² + a b + b²)→→→Option (D) is true option.
I will show you , how this identity is valid.
Taking R H S
(a-b)(a² +b²+ab)
= a (a² +b²+ab)-b(a² +b²+ab)
= a³ + a b² +a²b -b a² -b³ -ab²
Cancelling like terms , we get
= a³ - b³
= L H S